Prevalence and factors associated with utilization of emergency obstetric newborn care services among women of reproductive age in Nakuru county Kenya - Maingi, Nancy N.; Margaret, Keraka M.; Makworo, Drusilla G. (International Journal Of Community Medicine And Public Health, 2023)
Background: Emergency obstetric and newborn care (EmONC) mediates maternal survival. To prevent deaths, mothers require access to quality care and utilization of health facilities where professionals can promptly diagnose and manage emergencies related to pregnancy and childbirth. The study focused on socio-demographic, social cultural and social economic factors. Methods: The study was a randomized control trial and utilized a mixed method. Pregnant mother 26 to 32 weeks gestation and aged 15-49 years totaling to 382 respondents were enrolled in the study. Allocation to each study group was done on a 1:1 ratio; hence each group had 191 participants. The study was conducted from January to July 2020. Results: The intervention group had 95.93% (n=165) utilization of EmONC services in comparison to the control arm 75.29% (n=128). There was no discrepancy in both groups from base line to final survey OR=1.209, CI=0.742 to 1.969 and p=0.446. The level of education significantly influenced utilization at χ2=40.402 and a p<0.001. Secondary education influences utilization of EmONC services at AOR=8.791, 95% CI=3.631 to 21.285 and p<0.001. Respondents with tertiary education were 2.5 times likely to utilize EmONC services. Parity was significant at χ2=43.724, p<0.001. There was no significant difference between socioeconomic factors, sociocultural factors and utilization of EmONC services at baseline level. Conclusions: There was an increase in utilization of EmONC services. The education level and parity of the woman determined the utilization of EmONC services.